Acenocoumarol-related fatal in-utero subdural hematoma - Diogo, Mariana Cardoso (2017)
Fetal intracranial hemorrhages are typical of the germinal matrix, associated with fetal or placental problems. Subdural hemorrhages in utero are extremely rare but have been reported in coagulation disorders or maternal trauma. We present a case of atraumatic subdural hematoma in a 35 gestational week fetus, whose mother was under oral anticoagulation for prosthetic mitral valve. The mother complained of reduced fetal movement and ultrasound was inconclusive. Fetal magnetic resonance imaging (MRI) was performed the following day. MRI revealed an extensive subdural hematoma involving both hemispheric convexities and the tentorium, with significant mass effect. No heartbeat was detected in an US performed 1 day after MRI. Autopsy confirmed the diagnosis. To our knowledge it is the most extensive acenocoumarol-related in-utero SDH reported, and an excellent example of how fetal MRI might aid in prenatal diagnosis of fetal hemorrhagic complications.